Comparison Between Open Shouldice Versus Laparoscopic Unilateral Inguinal Hernia Repair: A Randomized Controlled Trial - Karim Bux, Jamshed Bashir, Ishfaq Ahmad Khan, Muhammad Bilal, Sandesh Kumar, Raja Muhammad Adeel Khan, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To compare the outcomes of laparoscopic Inguinal hernia repair and open Inguinal hernia Shouldice repair. Study design: A randomized controlled trial Place and duration: This study was conducted at Liaquat University of Medical Health Sciences Jamshoro, Pakistan from April 2020 to April 2021. Methodology: In this study comparison of a laparoscopic and open procedure was done. A total of 124 patients were included in the study. A total of 64 patients underwent a Laparoscopic Transabdominal Pre Peritoneal (TAPP) Inguinal Hernia Mesh Repair and 60 patients underwent the Shouldice technique of hernia repair which is an open surgical Non Mesh Technique. The measured Variable were Early Complication, Return to work, Duration of analgesia requirement and Reoccurrence Rate. The data were analyzed using IBM SPSS version 26. Results: The rate of complications in both groups was similar. Patients who underwent the laparoscopic procedure mean duration to return back to work was 12 days. On the other hand, those who had the Shouldice procedure mean duration was 17 days return back to work. The mean duration of analgesia intake after a laparoscopic procedure was 2.2 days and after a Shouldice procedure was 2.8 days. Recurrence of the hernia was reported by 3 (4.69%) patients who underwent the laparoscopic procedure and 2 (3.33%) patients who underwent the open procedure. Conclusion: The laparoscopic procedure is a better procedure than the open procedure of primary unilateral hernia repair in terms of early recovery, return to work and postoperative pain.